2017
DOI: 10.1101/174565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative analyses of splicing in the aging brain: role in susceptibility to Alzheimer’s Disease

Abstract: We use deep sequencing to identify sources of variation in mRNA splicing in the dorsolateral prefrontal cortex (DLFPC) of 450 subjects from two prospective cohort studies of aging. Hundreds of aberrant pre-mRNA splicing events are reproducibly associated with Alzheimer's Disease (AD). We also generate a catalog of splicing quantitative trait loci (sQTL) effects in the human cortex: splicing of 3,198 genes is influenced by genetic variation. sQTLs are enriched among those variants influencing DNA methylation an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
(104 reference statements)
0
12
0
Order By: Relevance
“…We next asked whether PD-associated variants were enriched among molecular (including expression, splicing, histone, and DNA methylation) quantitative trait loci (QTLs) in dorsolateral prefrontal cortex (DLFPC) 21,22 and immune cell-types 5,23 ( Fig. 1c).…”
Section: Heritability Enrichment Of Expressed Genes Identifies Pd-relmentioning
confidence: 99%
See 1 more Smart Citation
“…We next asked whether PD-associated variants were enriched among molecular (including expression, splicing, histone, and DNA methylation) quantitative trait loci (QTLs) in dorsolateral prefrontal cortex (DLFPC) 21,22 and immune cell-types 5,23 ( Fig. 1c).…”
Section: Heritability Enrichment Of Expressed Genes Identifies Pd-relmentioning
confidence: 99%
“…Individuals were genotyped on Illumina Human 610 Quad custom arrays.The gene expression data is available via https://ega-archive.org/studies/EGAS00001000411. (4) ROS/MAP RNA-seq data generation was previously described in22,21 . ROS/MAP is a prospective cohort of aging individuals, where individuals are healthy at enrollment and 38% have clinical Alzheimer's disease at the time of death.…”
mentioning
confidence: 99%
“…However, the precise gene-regulatory mechanisms and molecular pathways involved in AD progression remain to be elucidated. Case-control studies of differential gene expression in large postmortem brain cohorts have identified multiple genes and regulatory elements associated by AD [3][4][5] . The gene regulatory networks of these differentially-expressed genes have revealed promising associated genes for AD 3,4 , However, interpretation of case-control differential expression is challenging because it requires accounting for reverse causation of disease on gene expression, biological confounding, and technical confounding.…”
Section: Introductionmentioning
confidence: 99%
“…U1-70K is normally nuclear, but is found mislocalized to cytoplasmic Tau-immunoreactive neurofibrillary aggregates in AD neurons (6), which may contribute to a loss of spliceosome function given recently identified RNA splicing deficits in the disease (8). Mislocalization of other RBPs contributes to neurodegenerative disease (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…For example, U1 small nuclear ribonucleoprotein 70 kDa (U1-70K) and other core components of the spliceosome complex form detergent-insoluble aggregates in both sporadic and familial human cases of AD (5)(6)(7). Furthermore, RNA-seq analysis from AD and control brains revealed a significant accumulation of unspliced pre-mRNA disease related transcripts in AD consistent with a loss of U1-spliceosome function (7,8). Currently, our knowledge of the specific mechanisms underlying U1-70K aggregation is limited.…”
Section: Introductionmentioning
confidence: 99%